Genômica populacional de Handroanthus serratifolius e Tabebuia aurea - Vieira, Lucas Donizetti (2018)
Population genomics studies in Neotropical species are scarce, however, they are of great importance for the understanding of the neutral and adaptive variations, in order to develop strategies of management and conservation for the species. In this context our objective was to verify the role of natural selection in the distribution of populations diversity in Handroanthus serratifolius and Tabebuia aurea. Here, we study population genomics based in sequence capture using 24,751 pre-developed probes. For H serratifolius were sampled c. 64,000 SNPs in 144 individuals from 16 populations. For T aurea were sampled c. 18,000 SNPs in 48 individuals from 6 populations. Genetic differentiation was high (FST = 0.194, p <0.001) in H. serratifolius and intermediate (FST = 0.144, p <0.001) in T. aurea. The inbreeding coefficient was low in both species, however, in three populations of H. serratifolius it was intermediate or high. The genetic structure of populations presented two genetic groups for the populations sampled in the two species. H. serratifolius with high genetic differentiation and T. aurea with admixture in all populations. We did not find SNPs outliers in the distribution of FST values, due to the wide distribution of values found for the populations of the two species. In the search for correlation between environmental variables and changes in allelic frequency H. serratifolius presented only three SNPs, inside six genes and T. aurea presented 16 SNPs, inside 25 genes. The functional annotation of these genes showed relationship with molecular processes, transposable elements and one in T. aurea related to resistance to diseases. In conclusion, our data show a selection signal in H. serratifolius for only three loci with local adaptation signal. In T. aurea our data show a greater number of locos (16 locos) with local adaptation signal.